Reassessing the Bus Priority Lane and Exploring the Feasibility of BRT in Kathmandu - Dahal, Alok; Bhandari, Anup; Boyaju, Garima (International Journal on Engineering Technology and Infrastructure Development, 2025)
The rapid urbanization of Nepal’s cities has brought escalating challenges in managing urban mobility, such as severe traffic congestion, road deterioration, and increased vehicular emissions. Despite initial attempts to introduce a Bus Rapid Transit (BRT) system as a sustainable alternative, Kathmandu’s transport initiative launched a bus priority lane in 2023. However, it has been mischaracterized as a BRT system and has failed to achieve its intended objectives of reducing congestion and improved efficiency. This study critically evaluates the feasibility of implementing a true BRT system in Kathmandu, addressing the misconception highlighted by reviewers, and identifies key barriers such as inadequate infrastructure, operational inefficiencies, absence of Intelligent Traffic Systems (ITS), limited lane segregation, low public engagement, and fragmented governance. Utilizing a comparative case study approach, the research draws lessons from successful BRT implementations in Bogota (Colombia), Jakarta (Indonesia), and Ahmedabad (India), as well as failures in Delhi (India) and Dhaka (Bangladesh), to propose tailored solutions. Recommendations include innovative infrastructure designs for narrow roads, establishment of a dedicated transport authority, integration of ITS, and robust public awareness campaigns, aligned with the 2024 BRT Standard’s emphasis on gender inclusion, safety, and sustainability. These findings offer actionable insights for policymakers, demonstrating how a well-executed BRT system along Kathmandu’s Ring Road could enhance road longevity, traffic efficiency, passenger safety, and overall urban mobility in a developing country context.